Entrepreneurial Capital and Islamic Traditions: A Study of Barriers faced by Women Entrepreneurs in Punjab (Pakistan) - Saima Afzal; Ashfaq Ahmad Maan (Pakistan Journal of Islamic Research)
Women are playing their role side by side with men in all spheres of life. Muslim women have potential entrepreneurial capital and they can excel in their field if no barriers hold them back. This study was designed to investigate the barriers that hinder the progress of women entrepreneurs in a Muslim country like Pakistan. This study was qualitative by nature. It focused on the main objective to find the socio-cultural and economic barriers faced by women entrepreneurs in Punjab (Pakistan). It also focused to find the effects of Islamic traditions on the entrepreneurial behavior of the women entrepreneurs. For the aforementioned purpose, three focus group discussions were carried out in three districts (Rawalpindi, Faisalabad, and Lodhran) of Punjab province of Pakistan. Women entrepreneurs were found to be energetic and passionate about their enterprises. However, male dominance, restriction of ḥijāb/veil, less business networking with male business owners, restricted spatial mobility, authority and decision making, and access to finance were some socio-cultural and economic barriers found in detail discussion sessions. In the light of focus group discussions, it was suggested that a policy shift is a necessity of time. Islamic Sharī’ah provide all the basic rules for women to play their role as an active member of society and these rules are to be enforced through effective policies.